Síntese de 5-hidróxi-3-(1,1-dimetoxietan-2-il)-5-trifluormetil-2-pirazolinas e 3-(1,1-difluoretan-2-il)-1H-pirazóis análogos - Porte, Liliane Medianeira Favero (2008)
This work describes, at first, the synthesis of 4,6,6-trimethoxy-1,1,1-trifluorohex-3-en-2-one by the acylation reaction of 1,1,3,3-tetramethoxybutane, in 65% yields. Afterwards, the synthesis of a new series of 4,5-dihydro-1H-pyrazoles, which contain a ketal-protected aldehyde function as substituent, is described. These compounds are obtained by the reaction of 4,6,6-trimethoxy-1,1,1-trifluorohex-3-en-2-one with hydrazines (NH2NHR, R= 2-furoyl, C6F5, COOMe, COMe, Nicotinoyl), in 90-97% yields. In a subsequent step, dehydration reactions of 4,5-dihydro-1H-pyrazoles are reported, leading to 1H-pyrazoles. In addition, this work proposes a fluorination methodology of the ketal substituent of the 4,5-diidro-1H-pyrazoles and 1H-pyrazoles using diethylaminosulfur trifluoride (DAST). Finally, this work reports the desprotection of the ketal substituent to obtain the respective carbonyl compound and the subsequent fluorination reaction leading to the difluorinated analogues, in 55-60% yields. The compounds were characterized by 1H and 13C NMR experiments and by Mass Spectrometry, and their purity was confirmed by elemental analysis.